Caudate Functional Connectivity Associated With Weight Change in Adolescents - Nakamura, Yuko; Ozawa, Sachiyo; Koike, Shinsuke (Frontiers in Human Neuroscience, 2020)
Background: Childhood obesity has become a global epidemic and the etiology of maladaptive ingestive behavior in children warrants further research. Mounting evidence suggests that the caudate is associated with body weight gain and obesity in adults. In adolescents, however, how caudate related neural networks are associated with body weight gain is unclear because their central nervous systems are still developing. Objectives: The current longitudinal resting-state functional magnetic resonance imaging (rs-fMRI) study was conducted to investigate the hypothesis that caudate-related neural networks have a role in weight gain in adolescents. Methods: The study included 20 healthy adolescents with a mean age of 17.5 ± 2.0 years and a mean body mass index of 20.6 ± 2.1 who underwent baseline rs-fMRI then follow-up rs-fMRI approximately 1 year later. Body mass index (BMI) was measured at both timepoints. Seed-based functional connectivity analysis was utilized to analyze caudate-related functional connectivity (FC) using the caudate as a seed. Associations between caudate-related FC and BMI at baseline were assessed, as were associations between change in BMI and caudate-related FC between baseline and follow-up. Results: At baseline, greater caudate-lateral prefrontal cortex FC was correlated with lower BMI (family-wise error-corrected p < 0.05). Compared to the baseline, increased FC in the caudate-lateral prefrontal cortex at follow up were negatively associated with increased BMI (p < 0.05). Conclusion: Given that the lateral prefrontal cortex and caudate are associated with inhibitory control, the caudate-lateral prefrontal cortex FC may have a preventive effect on weight gain in adolescents. The results of the current study suggest that developing inhibitory control would lead to the prevention of childhood obesity.